Prostitution: reasons and future perspectives in a group of young girls (Revista Latino-Americana de Enfermagem, 1999)
This is a descriptive exploratory study developed at the city of Natal/RN, through interviews with 10 young girls that made sexual programs at the Meio and Ponta Negra beachs. The purpose was to identify the reasons that made young girls to opt for this activity and the future perspectives of this group. Authors identified that the principal cause that leads these kids to become prostitutes was the lack of financial conditions, and, also, that they believe in future, to be able to work, to leave the prostitution, to have a profession and a better life. Therefore, there is a need for decisions by the responsible agencies and for society in general to give alternatives to these young kids to leave prostitution and mainly to prevent the ingress of new adolescents in this activity.